EPIC MODEL: Pengukuran Efektifitas Komukasi Pemasaran Usaha Mikro Kecil dan Menengah di Kota Medan pada masa New Normal - Wili Chandra; Dewi Anggraini; Fauzi Akbar Maulana Hutabarat (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2022)
MSMEs are the largest contributor to GDP in Indonesia but are still constrained and have difficulty determining effective promotional media, especially during the current New Normal period so that they can survive and increase income from day by day. This study aims to determine the effectiveness of MSME online advertisements in Medan City which are displayed on social media. The results of this study are expected to be useful for MSMEs in Medan City to provide advertisements for these parties optimally so that they get the expected results. The data used in this study were obtained from 100 samples who are residents of Medan City and are social media users who have seen MSME advertisements on social media. The data analysis technique used is the EPIC method introduced by The Nielsen Company. Where the variables are empathy (empathy), persuasion (persuasion), impact (impact), and communication (communication). The results of the EPIC analysis for each variable were empathy = 3.715, persuasion = 3.855, impact = 3.7125, and communication = 3.9025. Of the four variables studied, if included in the effectiveness scale, the four results of the analysis of these variables are partially in the "effective" range. The EPIC rate value which is the average value of the four variables is at 3.79625. This value is in the “effective” range on the effectiveness scale range.